Analisis Penerbitan Sertifikat Kesehatan Kapal Tugboat PT Pelayaran Kartika Samudra Adijaya di Samarinda - Gloria Jelita Maharani Fangidae; Jumriani Jumriani; Abdul Rahman (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
Analysis of the Issuance of Health Certificates for Tugboats by PT Pelayaran Kartika Samudra Adijaya in Samarinda (supervised by Jumriani and Abdul Rahman). The purpose of this study was to analyze the factors causing delays in the issuance of tugboat health certificates and the relationship between internal and external factors influencing the delays in the issuance of ship health certificates by the Port Health Office (KKP). The study used a qualitative descriptive method with data collection techniques including observation, interviews, and documentation. Data analysis was conducted over a one-year period, from July 2024 to July 2025, at PT Pelayaran Kartika Samudra Adijaya. The results show that delays in the issuance of ship sanitation certificates are caused by internal and external factors. Internal factors include substandard ship sanitation conditions, such as poor cleanliness of the kitchen and bathrooms, as well as a lack of sanitation supervision by the crew. External factors are related to the inspection process conducted by the Port Health Office, which requires corrective actions and re-inspection when non-compliance is found. The relationship between these factors indicates that low sanitation readiness increases the likelihood of re-inspection, thereby delaying the issuance process of ship sanitation certificates.